2009
DOI: 10.4314/jmbr.v5i1.10679
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Undiagnosed Diabetes Mellitus Among Dental Patients in Edo State, Nigeria

Abstract: Systemic diseases and hormonal changes have been implicated as complicating factors for periodontal diseases 1 . Gingivitis and periodontitis are sometimes the first evidence that a patient has diabetes 2 . Given that diabetes may be present for a number of years before it is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…However, the relative merits of risk modelling were discussed with comparisons to the gold standard of biological screening as undertaken in the systematically reviewed studies ( Table ). Seven studies were excluded based on justifications presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…However, the relative merits of risk modelling were discussed with comparisons to the gold standard of biological screening as undertaken in the systematically reviewed studies ( Table ). Seven studies were excluded based on justifications presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported that about 5% of patients seeking medical advice at dental clinics are diabetics [ 9 ]. Other studies reported that around 4% of diabetic patients were first diagnosed with diabetes at dental clinic through their dental complications of diabetes [ 10 ]. The reason behind the relatively high prevalence of diabetes among dental patients is probably the bidirectional relationship between diabetes and dental ill-health [ 11 , 12 ].…”
Section: Diabetes Among Patients Seeking Orthodontic Treatmentmentioning
confidence: 99%
“…The prevalence of DM in South Western Nigeria is 4.76% with 2.38% as undiagnosed DM. [3] The prevalence of undiagnosed DM in the outpatient dental clinic of University of Benin Teaching Hospital (UBTH) and University College Hospital is 4.5% [4] and 4.4%, [5] respectively.…”
Section: Introductionmentioning
confidence: 99%